2021
DOI: 10.3390/ijms22179425
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Roles for Neurodevelopmental and Neuroendocrine Genes in Shaping GnRH Neuron Physiology and Deficiency

Abstract: Gonadotropin releasing hormone (GnRH) neurons are hypothalamic neuroendocrine cells that control sexual reproduction. During embryonic development, GnRH neurons migrate from the nose to the hypothalamus, where they receive inputs from several afferent neurons, following the axonal scaffold patterned by nasal nerves. Each step of GnRH neuron development depends on the orchestrated action of several molecules exerting specific biological functions. Mutations in genes encoding for these essential molecules may ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 242 publications
(327 reference statements)
0
25
0
Order By: Relevance
“…S3 " type="url"/> ). In our set-up, NRP1 , a gene implicated in the development of CHH ( Men et al, 2021 ; Oleari et al, 2021 ), has shown consistent upregulation upon treatment with FGF8. Interestingly, GnRH neurons in mice have been shown to express Nrp1 ( Vanacker et al, 2020 ), which is known to have a role in the migration of GnRH neurons ( Cariboni et al, 2011 ).…”
Section: Discussionmentioning
confidence: 67%
“…S3 " type="url"/> ). In our set-up, NRP1 , a gene implicated in the development of CHH ( Men et al, 2021 ; Oleari et al, 2021 ), has shown consistent upregulation upon treatment with FGF8. Interestingly, GnRH neurons in mice have been shown to express Nrp1 ( Vanacker et al, 2020 ), which is known to have a role in the migration of GnRH neurons ( Cariboni et al, 2011 ).…”
Section: Discussionmentioning
confidence: 67%
“…Reln , Cxcr7 ) (14) or with GD pathogenesis (e.g. Sema3a , Fgfr1 ) (4) emphasizes the efficacy of dissecting the genetic signatures of GnRH neurons in rodents to decipher the molecular mechanisms of GnRH neuron biology and to predict human disease genes.…”
Section: Discussionmentioning
confidence: 99%
“…NLGN3 belongs to the neuroligin family, a class of postsynaptic cell adhesion molecules which regulate synapse organization (10) and dendritic outgrowth (11), and NLGN3 missense variants have been so far associated with autistic spectrum disorder (ASD) (12). Thus, in this work we described two patients carrying novel nonsense NLGN3 variants and presenting with clinical features typical of GD and ASD, therefore providing the first genetic correlation between these two neurodevelopmental disorders, which was previously only implied by a registry-based association study (4).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…CHH is genetically a heterogeneous disorder with identified X-linked, autosomal dominant, and autosomal recessive patterns of inheritance. With the development of next-generation sequencing (NGS) techniques, pathogenic variants in more than 50 genes have been identified in CHH ( 3 ). However, each gene linked to CHH only seems to underpin a small percentage of total patients, so we are still far from achieving a comprehensive understanding of the genetic basis of CHH.…”
Section: Introductionmentioning
confidence: 99%